2005
DOI: 10.1002/adma.200500561
|View full text |Cite
|
Sign up to set email alerts
|

An Organic Field‐Effect Transistor with Programmable Polarity

Abstract: Organic thin-film field-effect transistors (FETs) have been studied extensively over the last decade, and tremendous progress in device performance has been achieved.[1] OrganicFETs have worked mainly as unipolar p-type transistors, in which positive charges are accumulated in the channel by applying a negative gate voltage, V G . As a result, the state-ofthe-art integrated circuits based on organic FETs are based on unipolar p-type logic.[2] For memory applications, organic transistors with a ferroelectric ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…4.12(b) clearly indicates a ferroelectric switching, although not as clear as for depletion voltages, since its superimposed with an increased DC current component. 78,79 Thus, it can be concluded that, the output characteristic starts to accumulate at voltages below V c , before the ferroelectric polarisation was reversed. The fact that I D (V DS ) does not reflect the ferroelectric switching may serve as a further confirmation for the existence of negative charges, which compensate the ferroelectric polarisation charge of the insulator.…”
Section: Effect Of Stable Ferroelectric Polarization On the Field-effmentioning
confidence: 98%
“…4.12(b) clearly indicates a ferroelectric switching, although not as clear as for depletion voltages, since its superimposed with an increased DC current component. 78,79 Thus, it can be concluded that, the output characteristic starts to accumulate at voltages below V c , before the ferroelectric polarisation was reversed. The fact that I D (V DS ) does not reflect the ferroelectric switching may serve as a further confirmation for the existence of negative charges, which compensate the ferroelectric polarisation charge of the insulator.…”
Section: Effect Of Stable Ferroelectric Polarization On the Field-effmentioning
confidence: 98%
“…Most of the organic memory transistors reported to date exploit the electric field induced remnant polarization in ferroelectric polymer films [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Inorganic ferroelectric FET memories have been studied for decades; a memory performance of practical value has been achieved in recent years [46,47].…”
Section: Ferroelectric Ofet Memorymentioning
confidence: 99%
“…200 at a gate bias of 2.5 V, one of 30 at zero gate bias and a retention time of three hours [33]. In 2005, Naber et al fabricated ferroelectric OFET memory devices containing the ferroelectric copolymer poly(vinylidene fluoride/ trifluoro-ethylene) (P(VDF/TrFE)) as a gate insulator and poly[2-methoxy, 5-(2′-ethyl-hexyloxy)-p-phenylene-vinylene] as a semiconductor [34,35]. The devices had an on/off ratio of 10 4 , with a programming time of 0.3 ms and a memory stability of more than 1 week.…”
Section: Ferroelectric Ofet Memorymentioning
confidence: 99%
“…Organic heterojunction diodes [28,29,70,[79][80][81] and transistors [82][83][84][85][86][87][88][89][90][91][92][93][94] have been fabricated with the crystalline ferroelectric P(VDF-TrFE). As the copolymer poly(vinylidene fluoride with trifluoroethylene) is ferroelectric, transistors, both fully organic heterojunctions [82][83][84][85][86][87][88][89][90][91][92][93][94] and hybrid heterojunctions with an inorganic semiconductor [95][96][97][98][99], exhibit gate voltage dependent hysteresis, indicating the potential of P(VDF-TrFE) copolymers for nonvolatile random access memory devices.…”
Section: Implications For the Futurementioning
confidence: 99%
“…As the copolymer poly(vinylidene fluoride with trifluoroethylene) is ferroelectric, transistors, both fully organic heterojunctions [82][83][84][85][86][87][88][89][90][91][92][93][94] and hybrid heterojunctions with an inorganic semiconductor [95][96][97][98][99], exhibit gate voltage dependent hysteresis, indicating the potential of P(VDF-TrFE) copolymers for nonvolatile random access memory devices. An example of this type of gate voltage dependent hysteresis for an organic heterojunction transistor fabricated with polyaniline as a p-layer [69,70] on top of P(VDF-TrFE 70:30) where the latter is the gate dielectric layer is illustrated in Figure 15.…”
Section: Implications For the Futurementioning
confidence: 99%